Metastatic prostate cancer with malignant ascites: A case report and literature review - Ani, Ifeanyi; Costaldi, Mark; Abouassaly, Robert (Canadian Urological Association Journal, 2013)
Malignant ascites from advanced prostate cancer is a rare entity with only few cases reported. It represents a poor prognosis. We report a case of a 57 year old African American male presenting with weight loss, lower urinary tract symptoms, and voiding dysfunction, found to be in renal failure with metabolic abnormalities associated with significant abdominal distention and pain. CT imaging showed ascites which was pathologically confirmed by immunostaining and cytological identification of malignant cells. Prostate biopsy identified high grade prostate cancer which responded to hormonal therapy with a significant decrease in serum prostatic specific antigen (PSA). Ascites was managed with paracentesis and renal failure with hemodialysis as needed.